COMPARING THE PERFORMANCE OF OSPF AND OSPF-MPLS ROUTING PROTOCOL IN FORWARDING TCP AND UDP PACKET - Miswar, Nur; Herman, Herman; Riadi, Imam (Informatika, Universitas Jenderal Soedirman, 2023)
Routing is an important process in computer networks, which involves selecting a path for packet data. The routing mechanism is governed by protocols at layer three of the OSI model or layer two of the TCP/IP model. Routing can be static or dynamic, with dynamic routing algorithms automatically determining the best path in the network. One commonly used dynamic routing protocol is Open Shortest Path First (OSPF), which automatically selects the optimal route for data packets based on received network topology information. The need for more advanced and scalable routing solutions led to the development of Multi-Protocol Label Switching (MPLS), introducing the concept of label switching for faster and more efficient data forwarding. This research aims to analyze the performance of OSPF and OSPF MPLS routing scenarios regarding TCP and UDP services. Through evaluation of Quality of Service (QoS) parameters, including throughput, packet loss, delay, and jitter. This study simulates the network using GNS3 software, with TCP and UDP services transmitted for durations of 15, 30, and 60 seconds. The results showed performance for both scenarios with an average index value of 3.75, indicating